Revealing internal flow behaviour in arc welding and additive manufacturing of metals. Issue 1 (December 2018) - Aucott, Lee; Dong, Hongbiao; Mirihanage, Wajira; Atwood, Robert; Kidess, Anton; Gao, Shian; Wen, Shuwen; Marsden, John; Feng, Shuo; Tong, Mingming; Connolley, Thomas; Drakopoulos, Michael; et al.
Abstract Internal flow behaviour during melt-pool-based metal manufacturing remains unclear and hinders progression to process optimisation. In this contribution, we present direct time-resolved imaging of melt pool flow dynamics from a high-energy synchrotron radiation experiment. We track internal flow streams during arc welding of steel and measure instantaneous flow velocities ranging from 0.1 m s−1 to 0.5 m s−1 . When the temperature-dependent surface tension coefficient is negative, bulk turbulence is the main flow mechanism and the critical velocity for surface turbulence is below the limits identified in previous theoretical studies. When the alloy exhibits a positive temperature-dependent surface tension coefficient, surface turbulence occurs and derisory oxides can be entrapped within the subsequent solid as result of higher flow velocities. The widely used arc welding and the emerging arc additive manufacturing routes can be optimised by controlling internal melt flow through adjusting surface active elements. Understanding what happens to the liquid in melt pools during welding and metal-based additive manufacturing remains a challenge. Here, the authors directly image internal melt pool dynamics using synchrotron radiation to show surface tension affects flow speed, orientation and surface turbulence.